1984
DOI: 10.1002/pssb.2221240164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxygen Centers on the Thermoluminescence of NaF Crystals

Abstract: The thermoluminescence (TL) of pure and doped NaF crystals has been intensively investigated for the last years, however, in many works the spectral distribution of the emission was not studied and the interpretation of the glow peaks is often contradictory /l/.This note gives some new results concerning the influence of oxygen ions o n the T L process. N a F single crystals were grown both in vacuum and air atmosphere from the reactive of high purity. All the samples were X-irradiated up t o l x l 0 R. The ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The spectrum can be roughly decomposed into eleven Gaussian type absorption peaks (dashed curves) at 193.0 (peak 1), 220.0 (peak 2), 255.0 (peak 3), 280.0 (peak 4), 342.4 (peak 5), 355.2 (peak 6), 380.0 (peak 7), 414.4 (peak 8), 504.1 (peak 9), 575.5 (peak 10) and 639.2 nm (peak 11), and the corresponding widths are 0.711, 0.640, 0.600, 0.400, 0.600, 0.300, 0.230, 0.246, 0.494, 0.450 and 0.350 eV, respectively. The peaks 1-4 and 6 are due to oxygen impurities, among which the peak 1 associates to O 2À color centers [9], the peaks 2 and 4 to O 2À -V a + complexes, the peak 3 to O 2 À color centers and the peak 6 was observed previously but unidentified [10]; the peaks 7 and 8 associate probably to remanent magnesium impurities [11]; the peaks 5 and 9-11 associate to F, M, N 1 and N 2 color centers [12], respectively. Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The spectrum can be roughly decomposed into eleven Gaussian type absorption peaks (dashed curves) at 193.0 (peak 1), 220.0 (peak 2), 255.0 (peak 3), 280.0 (peak 4), 342.4 (peak 5), 355.2 (peak 6), 380.0 (peak 7), 414.4 (peak 8), 504.1 (peak 9), 575.5 (peak 10) and 639.2 nm (peak 11), and the corresponding widths are 0.711, 0.640, 0.600, 0.400, 0.600, 0.300, 0.230, 0.246, 0.494, 0.450 and 0.350 eV, respectively. The peaks 1-4 and 6 are due to oxygen impurities, among which the peak 1 associates to O 2À color centers [9], the peaks 2 and 4 to O 2À -V a + complexes, the peak 3 to O 2 À color centers and the peak 6 was observed previously but unidentified [10]; the peaks 7 and 8 associate probably to remanent magnesium impurities [11]; the peaks 5 and 9-11 associate to F, M, N 1 and N 2 color centers [12], respectively. Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Unfortunately, we have not found current investigations devoted to the study of the role of oxygen in the TL of NaCl crystals, but a recent study [24] dealt with the in°uence of oxygen centers on the TL of NaF crystals, where it was reported that oxygen centers (mostly O 2¡ v + a complexes) can stabilize interstitial halogen atoms (H centres). This is important, in particular, for the ion model of Alvarez Rivaz et al [20,21].…”
Section: ¡1mentioning
confidence: 99%